O desaparecimento de crianças e adolescentes - Neumann, Marcelo Moreira (2010)
The disappearance of people, especially children and adolescents awakens a lot of commotion in the society, however scientific studies on the subject are still rare. These few studies do not provide a deep reflection of the conceptual point of view. There is the 'disappearance' is reduced by the relation of cause and effect. The objective of this study was to expand the concept by the visions of sociology, law, psychology and literature, then treat it in its etymological sense. It was found that the origin of the word existing social elements that constitute it, the loss can only occur in human social relationships - in which it is perceived, seen and felt. After delineating the conceptual effort to relate the disappearance of their multiple determinations, highlighting the social causes, natural and psychological. In the social determinations were discussed the historical, cultural, religious, social issues, violence and the influence of totalitarian regimes in the disappearance of people. In natural determinations were shown how people disappear because of natural forces and human action. Discussed the formation of the individual and subjectivity and how these may influence psychological determinations in cases escape of the home or institution. The proposed investigation of the disappearance of children and adolescents from these multiple measurements, with the predominance of social determinations. The following is characterized by participation of those involved in these disappearances, based in some cases assisted by the ´Projeto Caminho de Volta´ - FMUSP. The data obtained from medical records were analyzed and categorized, which resulted in ' table expected behaviors' those involved in the situation of disappearance. These tables show the actions taken by each of the subjects involved soon after the disappearance of children and adolescents. They reveal the kind of relationship - the difficulties and pains of those seeking the missing, as well as the likely reasons for this. In the last chapter were discussed current challenges and perspectives of the topic, related to Brazilian public policy, moving tentatively in consolidating the legal framework for the disappearance in the country. Concluded that when considering the disappearance as a predominantly social situation, removes the load placed by society in missing or their families and forth this universalizing the issue, showing that the problem should be tackled by all